The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adfm.202204899
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Visualized Sensors for Peritoneal Dialysis Catheter Infection

Abstract: Peritonitis is a common complication for patients with end-stage renal disease undergoing peritoneal dialysis (PD) and is a direct cause or contributor in >15% deaths in PD patients. Since early detection is key to treatment, patients and their care teams need rapid, on-site diagnostics. A hydrogelbased peritoneal fluid pH sensor attached to a peritoneal dialysis catheter is developed to measure local acidosis indicative of peritoneal infections for early detection and monitoring of infections using X-ray imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…The sensor was only tested in vitro and for future in vivo applications it will need to be tested in a live animal. We recently used an X-ray visualized pH sensor to measure peritoneal pH during infection in a 2-week rat peritoneal dialysis model, [49] and found negligible drift through the period and postmortem. This is consistent with previous studies, where we found the hydrogels to be robust even during long-term incubation in oxidative environments.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor was only tested in vitro and for future in vivo applications it will need to be tested in a live animal. We recently used an X-ray visualized pH sensor to measure peritoneal pH during infection in a 2-week rat peritoneal dialysis model, [49] and found negligible drift through the period and postmortem. This is consistent with previous studies, where we found the hydrogels to be robust even during long-term incubation in oxidative environments.…”
Section: Limitationsmentioning
confidence: 99%
“…Previously, we developed hydrogel-based pH sensors to measure the pH of synovial fluid for early detection of hip infections and the pH of peritoneal fluid for peritoneal dialysis catheter infections using X-ray imaging. [48,49] Although no fouling effect on the sensor calibration curve, response rate or sensor degradation was observed in solutions of tryptic soy broth bacterial cell culture, bovine synovial fluid, bovine serum, highly oxidative hydrogen peroxide, and copper ion medium, or storage in pH 7 buffer, [50] biofouling maybe a potential concern for an indwelling sensor (especially over long periods (a hip prosthesis may last decades). We modified the pH sensor to determine CO 2 levels in synovial fluid with the added advantage of an improved lifetime by encasing the sensor and fluid in a CO 2 -permeable membrane which is impermeable to aqueous molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor has a hyperintense signal in MR images that attenuates with increasing local temperature [25]. Besides MRI, X-ray compatible sensors have also been investigated in prior work on implantable x-ray-based blood pressure microsensor for coronary stent monitoring [26] and X-ray visualized sensors detecting infection within the peritoneal dialysis catheter [27].…”
Section: Introductionmentioning
confidence: 99%